Edible Spoon and Edible Straw: Smart Solutions for Reducing Plastic Waste in Jombang, East Java: Edible Spoon and Edible Straw: Smart Solutions for Reducing Plastic Waste in Jombang, East Java - Adinda Zakia; Aprilia Asya Putri; I'in Noviana (LPPM STIKES Guna Bangsa Yogyakarta, 2024)
Plastic is a polymer compound whose main constituent elements are carbon and hydrogen. Because it is difficult to decompose in nature, plastic is the biggest contributor to waste which causes damage to the natural balance. Based on data from the National Waste Management Information System (2023), Plastic waste is the second most common type of waste after food waste, as many as 41.1%. The solution to banning the use of plastic spoons and straws has been found by creating environmentally friendly spoons and straws that are edible and biodegradable. This biodegradable (Edible Spoon) uses wheat flour as a base so it is safe for consumption. Edible and biodegradable straws (Edible Straw) are also made from natural ingredients, namely cassava flour (mocaf) and cornstarch. The method used to produce Edible Straw is the fruit peel method. The method used to produce Edible Straw is the fruit peel method. This method is used to make Edible Straw dough from a mixture of dough and fruit which is mashed into a thin sheet resembling skin. This community service was carried out by STIKES PEMKBAB Jombang students with the aim of reducing the amount of plastic waste, especially plastic spoon and straw waste in Jombang.